2022
DOI: 10.1017/dmp.2021.367
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Michael and Adverse Birth Outcomes in the Florida Panhandle: Analysis of Vital Statistics Data

Abstract: Objective: The aim of this study was to examine birth outcomes in areas affected by Hurricane Michael. Methods: Vital statistics data of 2017–2019 were obtained from the state of Florida. Births occurring in the year before and after the date of Hurricane Michael (October 7, 2018) were used. Florida counties were divided into 3 categories reflecting extent of impact from Hurricane Michael. Birth outcomes including incidence of preterm birth (PTB), low birth weight (LBW), and small for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Previously, we used the vital statistics data and county level FEMA assistance levels as a proxy of hurricane related exposures to compare births outcomes in the year before and after Hurricane Michael in the same study area. We found that Hurricane Michael was associated with a higher risk of LBW and SGA in the year after Michael compared to the year before but using county level FEMA [43]. However, we failed to identify associations between the extent of residential building damage and the risk of adverse perinatal outcomes in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…Previously, we used the vital statistics data and county level FEMA assistance levels as a proxy of hurricane related exposures to compare births outcomes in the year before and after Hurricane Michael in the same study area. We found that Hurricane Michael was associated with a higher risk of LBW and SGA in the year after Michael compared to the year before but using county level FEMA [43]. However, we failed to identify associations between the extent of residential building damage and the risk of adverse perinatal outcomes in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…Cyclone-related preterm birth risks were reported in seven studies, 16 18 , 87 90 and two of them observed statistically significant higher risks among the women who experienced a hurricane during pregnancy. 18 , 89 However, a null association was found in the other four studies on a high-amplitude hurricane 16 , 87 , 88 or 58 tropical cyclones. 17 One cross-sectional study with 647,634 births in Queensland, Australia, examined the association of trimester-specific cyclone exposure with preterm birth and found that only tropical cyclone exposure in early pregnancy was associated with higher odds of preterm births.…”
Section: Resultsmentioning
confidence: 79%
“… 17 One cross-sectional study with 647,634 births in Queensland, Australia, examined the association of trimester-specific cyclone exposure with preterm birth and found that only tropical cyclone exposure in early pregnancy was associated with higher odds of preterm births. 90 Four 17 , 18 , 87 , 88 of these seven studies on preterm birth that reported relative change in the risk of preterm birth associated with cyclones (i.e., exposed vs. unexposed) were included in the meta-analysis, whereas the other three studies 16 , 89 , 90 were not included because one of them reported only the trimester-specific effect estimate, 90 one reported absolute change in the incidence rate, 89 and the remaining one used a continuous cyclone exposure level based on self-reported cyclone experience. 16 An overall statistically insignificant association [meta- (95% CI: 0.91, 1.29); Figure 3 ] with high heterogeneity ( , ) and statistically insignificant asymmetry (Figure S4; Egger’s regression test, ) were found between cyclone exposures and preterm births.…”
Section: Resultsmentioning
confidence: 99%
“… 4 , 5 In the United States, 60.2 million people live in hurricane-prone areas, 6 and damages due to hurricanes have risen considerably over the last century, mainly due to increases in population and wealth in hurricane-affected areas. 7 , 8 Prior studies suggest exposure to a hurricane during pregnancy may be associated with an increased risk of adverse birth outcomes, 9 including preterm birth, 10 , 11 fetal distress, 12 low birth weight, 11 , 13 and small for gestational age birth. 13 Leading explanations include stress 14 and limited access to prenatal care.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Prior studies suggest exposure to a hurricane during pregnancy may be associated with an increased risk of adverse birth outcomes, 9 including preterm birth, 10 , 11 fetal distress, 12 low birth weight, 11 , 13 and small for gestational age birth. 13 Leading explanations include stress 14 and limited access to prenatal care. 15 However, the evidence is not consistent, with some studies reporting a null or protective effect for preterm birth and low birth weight.…”
Section: Introductionmentioning
confidence: 99%